Internalization: what does it tell us about pharmacokinetic and pharmacodynamic properties of an antagonist? - Mueller, A (Nature Publishing Group, 2007)
Chemokine receptors play an important role in trafficking leukocytes within the body, a process that depends on expression of the receptors on the cell surface. Expression levels are regulated by the rate of internalizing receptor compared to the rate of recycling/recovering receptor. Internalization is commonly induced by binding of agonists to their receptors that in turn use clathrin-coated pits or caveolae to internalize. Joplin and colleagues describe a novel usage of internalization assays to determine pharmacokinetic/pharmacodynamic relationships of an antagonist on CXCR3 in a murine system. Intriguingly their results show that internalization assays give robust data about the pharmacokinetics/pharmacodynamics of different agonists and antagonists in an in vivo model. This kind of assay will allow investigations of the pharmacological properties of agonists and antagonists in a completely different setting and also give new insight into the regulation of cell surface expression of chemokine receptors and other G protein-coupled receptors, which can lead to potential novel therapeutic targets.